Deterministic Safety Technology for RBMK Reactors - F. D'Auria; S. Soloviev; D. Mazzini; C. Sollima (Science and Technology of Nuclear Installations)
The present paper deals with the description of the technical activities conducted within the TACIS Project R2.03/97, 2 EC Contract no. 30303, related to RBMK. The project activities are focused toward the setting-up of a chain of computational tools suitable for the analysis of transients expected in the RBMK nuclear power plant (NPP). The accident leading to the rupture of one pressure channel, with fuel melting or high temperature damage, creep and brittle failure of the pressure tube and of graphite bricks with possibility of rupture propagation, constitutes the reference scenario for the project. However, a series of expected scenarios has been selected to prove the capability of the individual codes or chains of code in simulating the envisaged phenomenology. The paper summarizes the activities performed at NIKIET in Moscow and at University of Pisa (UNIPI) in Pisa. A top-down approach is pursued in structuring the executive summary that includes the following sections: (i) the safety needed for the RBMK NPP, (ii) the roadmap, (iii) the adopted computational tools, (iv) key findings, (v) Emphasis is given to the multiple pressure tube rupture (MPTR) issue and the individual channel monitoring (ICM) proposal.